(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Phacoemulsification is a frequent cataract surgery method nowadays. The loss of corneal endothelial cells during phacoemulsification is influenced by the degree of nucleus sclerosis. Irrigation flow, fluid turbulence and movement, air bubbles, direct trauma from instruments or lens fragments, and the time and power required to complete nuclear emulsification are other factors that might result in endothelial cell injury during phacoemulsification. Methods: Our study included 90 patients after taking approval from Ethical Review Committee from 1st May 2024 to 31st October 2024. Patients were selected for the data collection process in the Eye outpatient department. Slit lamp examination was performed on all patients to diagnose cataract. Spectrum microscopy was done to examine endothelial cell count before and after phacoemulsification in grade 2 versus grade 4 nuclear sclerosis cataract. Patients were divided into two groups based on the grade of nuclear sclerosis cataract: Group A (patients with grade 2 nuclear sclerosis cataract) and Group B (patients with grade 4 nuclear sclerosis cataract). Results: The mean age of patients was 61.311±3.97 years in Group A and 62.400±3.58 years in Group B. The mean ±SD of baseline endothelial cell count in Group A was 2248.022 ±132.05 mm2 while in Group B was 1977.488 ±180.90 mm2 (p-value <0.001). The mean ±SD of postoperative endothelial cell count after 6 weeks in Group A was 1935.622 ±165.57 mm2 (mean cell loss 312.4 mm2) and Group B was 1535.955 ±177.37 mm2 (mean cell loss 441.5 mm2 ;p-value <0.001). Difference in baseline endothelial cell count between the two grades of nuclear sclerosis cataract was 270.53 mm2 which increased to 399.66 mm2 after 6 weeks following phacoemulsification (p-value <0.001). Conclusion: Endothelial cell loss was higher with high grade of nuclear sclerosis cataract ranging from 13.89% in grade 2 to 22.32% in grade 4 with average cell loss of 8.43%.